1998
DOI: 10.1046/j.1365-2559.1998.00348.x
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein and apoptosis in primary human hepatocellular carcinoma and metastatic adenocarcinoma

Abstract: These results suggest a relationship between absence of MT and appearance of APPC in human liver tumours, especially in metastatic adenocarcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
1
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 35 publications
(46 reference statements)
2
20
1
1
Order By: Relevance
“…In hepatocellular carcinoma, a decrease in the intensity of immunohistochemical staining has been reported for metallothioneins. 36,37 Metallothioneins were also found to be downregulated in hepatocellular carcinoma in a global mRNA expression analysis by Okabe et al, 30 concordant with our results. In patients suffering from hepatocellular carcinoma, metallothioneins were measured in serum, and the concentration correlated inversely with the grade of differentiation of hepatocellular carcinoma.…”
Section: -31supporting
confidence: 91%
“…In hepatocellular carcinoma, a decrease in the intensity of immunohistochemical staining has been reported for metallothioneins. 36,37 Metallothioneins were also found to be downregulated in hepatocellular carcinoma in a global mRNA expression analysis by Okabe et al, 30 concordant with our results. In patients suffering from hepatocellular carcinoma, metallothioneins were measured in serum, and the concentration correlated inversely with the grade of differentiation of hepatocellular carcinoma.…”
Section: -31supporting
confidence: 91%
“…Previously, a similar downregulation of MT expression has been reported in metastatic lymph nodes from human breast cancers [29]. Also, Deng et al [30]reported that the primary hepatocellular carcinomas showed moderate MT staining with a small number of apoptotic cells while metastatic adenocarcinomas showed no MT staining with a large number of apoptotic cells. Therefore, it seems that altered MT expression in the metastatic tumor is produced by some kind of phenotypic change due to the change in the tumor environment, or it might be possible that the MT-negative metastatic tumor cells are derived from a pool of heterogeneous cells with variable MT expression in the primary tumor.…”
Section: Discussionsupporting
confidence: 68%
“…Recently, some studies have suggested that the degree of MT expression may affect apoptotic processes in certain normal and tumor cells and the incidence of apoptosis may differ with alteration in MT expression. 33,34) Deng et al 35) reported a negative correlation of MT with the incidence of apoptotic cells in human primary hepatocellular carcinomas and metastases, possibly associated with inhibition of apoptotic transduction signals. Further, Penkowa et al 36) proposed that MT may inhibit apoptotic cell death in the central nervous system of female Lewis rats.…”
Section: Discussionmentioning
confidence: 99%